Pull-off testing as an interfacial bond strength assessment of CFRP-concrete interface exposed to a marine environment. (August 2018) - Fazli, Hamed; Yassin, A.Y. Mohd; Shafiq, Nasir; Teo, Wee
Abstract: The long-term performance of the bond between carbon fibre reinforced polymer composite (CFRP) fabrics and concrete substrate is crucial to estimations of the reliability of externally strengthened concrete structures. This paper presents the experimental results and analysis of 162 pull-off tests using nine concrete slabs under various environmental conditions, i.e., wet/dry cyclic exposure and full-immersion exposure of 3.5% salt-water at a temperature of 60 °C. The main objective of this study was to assess the effects on the bond performance of CFRP-strengthened concrete slabs during 12 months of exposure in a marine environment. Five types of failure modes were observed in the tested samples. The test results confirmed that 12 months of exposure in a marine environment had a low effect on the epoxy performance between CFRP and concrete. The results also indicated the marginal increase of pull-off strength values after 12 months of environmental exposure.